The challenge of dealing with non-AIDS comorbidities for people living with HIV: Perspectives and experiences of patients and healthcare providers - Julia Maria van Koeveringe; Elizabeth Liaño Callahan; Mala George; Teklu Teshome Russo; Biruk Seifu; Mark Spigt (Taylor & Francis Group, 2023)
As the cohort of People Living with HIV (PLHIV) ages, so does the spectrum and burden of non-AIDS define HIV-associated conditions (NARC). PLHIV are likely to need different and increased healthcare services. It requires health systems to adapt to this disease trend and conform to a chronic care model, which respects the distinct needs of the ageing population. In this article, we explore the lived experiences of PLHIV and their healthcare providers in managing the challenges of dealing with NARC in Arba Minch, Southern Ethiopia. This study utilises interpretative substantive methods, encompassing qualitative interviews and Focus Group Discussions. The Normalisation Practice Theory (NPT) guided the semi-structured questions concerning routine screenings and current models of HIV care for ageing individuals. The main structural challenges in providing adequate geriatric care included: (i) the lack of awareness of the risk of NARCs; (ii) the absence of blended care; (iii) an HIV-centred approach exclusive of multidisciplinary care; and (iv) financial constraints. In an era with increasing NARCs, traditional HIV care models must adapt to the emerging challenges of a 'greying' and growing population.